Vision‐related quality of life according to location of visual field loss in patients with glaucoma. Issue 5 (17th January 2019) - Chun, Yeoun Sook; Sung, Kyung Rim; Park, Chan Kee; Kim, Hwang Ki; Yoo, Chungkwon; Kim, Yong Yeon; Park, Ki Ho; Kim, Chan Yun; Choi, Kyu‐Ryong; Lee, Kyoo Won; Han, Seungbong; Kim, Chang‐sik; et al.
Abstract: Purpose: To assess influence of the location of visual field (VF) loss on vision‐related quality of life (VRQOL) in patients with glaucoma. Methods: We included 826 patients with primary open‐angle glaucoma (POAG) enrolled in the prospectively designed Life Quality of Glaucoma Patients Who Underwent Treatment (LIGHT) study organized by the Korean Glaucoma Society. We divided the integrated binocular visual field (IVF) into four regions and evaluated the associations between Rasch‐analysed 25‐item National Eye Institute Visual Function Questionnaire (NEI VFQ‐25) and location of the IVF using univariate and hierarchical multivariable linear regression. Results: Mean deviation (MD) of the IVF at superior centre showed the lowest value among the four regions. Multivariable linear regression analysis revealed significant correlation of the composite score and all subscales of the NEI VFQ‐25 except ocular pain and near activities at each of four IVF regions. Mean deviation at superior centre showed significant correlation with composite score ( R 2 = 0.181), near activities ( R 2 = 0.175), and social functioning ( R 2 = 0.166); MD at superior periphery showed highest correlation with role difficulties ( R 2 = 0.137); MD at inferior centre showed highest correlation with driving ( R 2 = 0.145); and MD at inferior periphery showed significant correlation with distance activities ( R 2 = 0.214) and dependency ( R 2 = 0.119). Conclusion: Four different regions of the IVF had a similarly important impact on subscales of the NEI VFQ‐25 in glaucoma patients. Preservation of the superior field should be considered as much as that of the inferior field for maintaining a good VRQOL in patients with glaucoma.